Development and In Vitro Characterization of a Sustained-Release Pirfenidone Matrix Tablet Using Hydrophilic and Hydrophobic Polymers: Research Article (Journal of Pharma Insights and Research, 2025)
Pirfenidone, a primary therapeutic agent for Idiopathic Pulmonary Fibrosis (IPF), has a short biological half-life that requires frequent daily dosing, often leading to non-adherence and adverse effects. This work is focused on the development of a matrix-based sustained-release (SR) tablet to prolong drug release over 12 hours. Tablets were prepared by direct compression, utilizing different concentrations of hydrophilic polymers (HPMC K15M, HPMC K4M) and a hydrophobic polymer (Eudragit RS 100) as release-retarding agents. Nine formulations (F1-F9) were systematically developed. Pre-compression evaluations confirmed that all powder blends exhibited good to excellent flow properties. Post-compression analysis showed that all tablet formulations complied with pharmacopoeial standards for weight variation, hardness, friability, and drug content uniformity. Drug-excipient compatibility was confirmed via Fourier Transform Infrared (FTIR) spectroscopy. In vitro dissolution studies, conducted in sequential pH media (0.1N HCl followed by pH 6.8 phosphate buffer), revealed distinct polymer-dependent release profiles. HPMC K4M, a low-viscosity grade, failed to sustain release, whereas Eudragit RS 100 provided significant retardation, resulting in incomplete release at higher concentrations. Formulation F1, containing HPMC K15M, achieved the target release profile, liberating 94.98% of the drug over 12 hours. The release kinetics for F1 were best described by the Higuchi model, indicating a diffusion-controlled mechanism. This formulation presents a viable platform for a reduced-dosing regimen of pirfenidone, offering potential for improved patient compliance.